1989
DOI: 10.1093/oxfordjournals.aje.a115125
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Report Bias in a Case-Control Study of Pregnancy Outcome

Abstract: The role of report (recall) bias in case-control studies of possible reproductive hazards was investigated in a study of women who gave birth at the Royal Victoria Hospital, Montreal from September 1983 to May 1985. Women were questioned twice (early in pregnancy; after delivery) about exposures that might influence pregnancy outcome. The two sets of responses of case mothers, control mothers, and mothers of infants of intermediate health status were then compared. Similar inconsistencies in the reporting of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
62
1

Year Published

1989
1989
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(64 citation statements)
references
References 0 publications
1
62
1
Order By: Relevance
“…Our assumption that 30% of exposed control mothers did not report exposure is likely too high; the magnitude of underreporting is probably smaller. Previous studies have shown that recall bias might not have as considerable an effect in practice as one might expect (Zierler and Rothman, 1985;Mackenzie and Lippman, 1989;Drews et al, 1990;Khoury et al, 1994). In the NBDPS, we study a number of different medications, including antidepressant exposures, and previous NBDPS studies have not observed a broad increase in the number of elevated associations with birth defects.…”
Section: Discussionmentioning
confidence: 98%
“…Our assumption that 30% of exposed control mothers did not report exposure is likely too high; the magnitude of underreporting is probably smaller. Previous studies have shown that recall bias might not have as considerable an effect in practice as one might expect (Zierler and Rothman, 1985;Mackenzie and Lippman, 1989;Drews et al, 1990;Khoury et al, 1994). In the NBDPS, we study a number of different medications, including antidepressant exposures, and previous NBDPS studies have not observed a broad increase in the number of elevated associations with birth defects.…”
Section: Discussionmentioning
confidence: 98%
“…Under-reporting was positively associated with periconceptional employment and over-reporting with education level. These are novel findings because very few studies have investigated the association of these characteristics with over-and underreporting of environmental exposures (Feldman et al, 1989;Mackenzie and Lippman, 1989;Little, 1992). Misreporting of residential proximity was also associated with geographic region.…”
Section: Discussionmentioning
confidence: 97%
“…While differential recall is often alleged and cited as a potential study limitation, rarely does the opportunity exist to assess the presence and magnitude of bias in effect estimation since a gold standard to validate self-reported exposures is usually lacking (Raphael, 1987;Swan et al, 1992). Furthermore, while previous validation studies of environmental exposures focused on identifying differential recall between case and control parents, these studies did not evaluate potential exposure over-reporting and under-reporting associated with geographic and demographic characteristics of study participants (Feldman et al, 1989;Mackenzie and Lippman, 1989;Little, 1992;Infante-Rivard and Jacques, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…As high risk pregnancies tend to be referred to tertiary centres for their care and delivery this method is likely to lead to bias, in that high risk pregnancies will be over represented in the population available for selection as controls and thus the estimated odds ratio will tend towards the null (Klebanoff and Rhoads, Introduction -Epidemiological methods has been much controversy about this subject in the literature, the substance of which is primarily the systematic reporting differences (ie. recall bias) of exposure between cases and 'normal' controls (Paganni-Hill and Ross, 1982), (Klemetti and Saxen, 1967), (Tilley, 1985), (MacKenzie and Lippman, 1989), (Werler et al 1989). However, there is rarely a 'gold standard' for comparison.…”
mentioning
confidence: 99%